First Dominant Circulation of Influenza A/H3 among Patients with Acute Respiratory Tract Infections in a Tertiary Care Hospital in Dhaka 2022 - Rahman, Mizanur; Ayaz, KFM; Islam, Sadiqul; Hasan, Nazmul; Rahim, Rummana; Hasan, Abu (Journal of Medicine, 2023)
The seasonal circulation of influenza viruses varies from year to year. We have retrospectively analyzed our hospital data of respiratory pathogens among patients of respiratory tract infections and extracted circulation of influenza viruses and characterized patients with influenza attended to a tertiary care hospital in Dhaka from July 2021 to September 2022. We have analyzed data of real-time reverse transcription polymerase chain reaction testing of respiratory panel done in QIAstatDx (Qiagen, Germany) using nasopharyngeal samples to identify the presence of influenza viruses and to determine the subtypes. A total of 547 patient’s data were analyzed in this study, with an influenza positivity rate of 15.62% in 2021 and 23.63% in 2022. We identified an exclusive circulation of influenza A/H3 viruses in 2022 while cocirculation of Influenza A (H1N1 pdm 09 – 10.15%, H3– 2.34%, A not subtyped – 2.34%) and influenza B (0.78%) was observed in 2021 in our cohort. Further, subtyping data showed that both Influenza A/H1N1 pdm09 and Influenza A/H3 was equally observed in influenza like illness (ILI) and severe acute respiratory infection (SARI) patients. This small study in our cohort warrants further elaborate investigation to know circulating influenza A subtyping in the country which may assist health care providers in making treatment decisions and hence, appropriate patient management. J MEDICINE 2023; 24: 37-42